PENINGKATAN KEMAMPUAN PESERTA DIDIK DALAM MENGIDENTIFIKASI AKOR MUSIK DENGAN TEKNIK ‘TUPATMA’ - Rus Endarti (BBPPMPV Seni dan Budaya Yogyakarta, 2021)
Identifying music chords is one of the students’ abilities in developing their creativity when learning Cultural Arts as the school subject. The mostly encountered problem at school is that students are less motivated to develop their ability to create music arrangement since they consider Cultural Art as a school subject proposed for only talented students. The current research aims at increasing the students’ ability to identify music chords using the technique of ‘Tupatma’ through direct instruction model. The classroom action research was carried out in two cycles including the stages of planning, implementation, observation, and reflection in each cycle. Subjects were tenth graders of Food Technology Class 1 in SMKN 2 Godean in the academic year of 2017/2018. Data collection techniques included observation, questionnaire, documentation, and field notes, while data analysis employed the technique of quantitative descriptive analysis. The result of the study demonstrates that the use of ‘Tupatma’ technique through direct instruction model can improve the average score of students’ learning completion rate in each cycle. Students’ average score in cycle 1 is 76.72 with the mastery percentage of 72%; and in cycle II students’ average score becomes 81.75 with the mastery percentage of 100 %.